Knowing - Black, Todd.; Pearson, Ryne Douglas; Snowden, Juliet, 1966-; White, Stiles; Proyas, Alex, 1963-; Cage, Nicolas, 1965-; Byrne, Rose.; Canterbury, Chandler; Robinson, Lara.; Mendelsohn, Ben.; Escape Artists (Firm); Mystery Clock Cinema (Firm); et al. (Universal City, Calif: Summit Entertainment, 2009)
In 1959, as part of the dedication ceremony for a new elementary school, a group of students is asked to draw pictures to be stored in a time capsule. One mysterious girl fills her sheet of paper with rows of apparently random numbers instead. Fifty years later, a new generation of students examines the capsule's contents and the girl's cryptic message ends up in the hands of Caleb. But it is Caleb's father, professor John Koestler, who makes the startling discovery that the encoded message predicts with pinpoint accuracy the dates, death tolls and coordinates of every major disaster of the past 50 years. With the reluctant help of the daughter of the now- deceased author of the prophecies, John's increasingly desperate efforts take him on a race against time until he finds himself facing the ultimate disaster and the ultimate sacrifice.
Widescreen.
Special features: Audio commentary with director Alex Proyas; Knowing all: the making of a futuristic thriller; Visions of the apocalypse.
Director of photography, Simon Duggan ; editor, Richard Learoyd ; music, Marco Beltrami ; costume designer, Terry Ryan ; production designer, Steven Jones-Evans.
Nicolas Cage, Rose Byrne, Chandler Canterbury, Lara Robinson, Ben Mendelsohn.
MPAA rating: PG-13; for disaster sequences, disturbing images and brief strong language.
DVD; Dolby digital 5.1.
Keywords: Time capsules -- United States -- Drama; Prophecies -- Drama; Disasters -- Drama; College teachers -- United States -- Drama; Fathers and sons -- United States -- Drama; Thrillers (Motion pictures); Action and adventure films; Films for the hearing impaired; Feature films; Science fiction films; Fantasy films